Clinical Predictors of Escherichia coli Versus Staphylococcus aureus Bacteremia at the Emergency Department - Pariwat Phungoen; Thanat Tangpaisarn; Kittisak Sawanyawisuth (Antibiotics)
Background: Bacteremia is a life-threatening condition encountered in the emergency department (ED). Escherichia coli and Staphylococcus aureus are among the most common pathogens, but early differentiation is challenging. Identifying clinical predictors may help guide empirical treatment while awaiting culture results. Methods: This retrospective analytical study included adults aged 18 years or older who presented with bacteremia in the ED between 1 January 2016 and 31 December 2018 and had blood cultures positive for either S. aureus or E. coli. Clinical predictors of E. coli bacteremia were identified using multivariable logistic regression analysis. Results: Among 327 patients, 272 (83.2%) had E. coli bacteremia. Significant predictors of E. coli bacteremia included hypertension (adjusted OR 2.12; 95% CI: 1.03–4.39; p = 0.041), solid organ tumor (adjusted OR 3.72; 95% CI: 1.63–8.51; p = 0.002), and higher body temperature (adjusted OR 1.49 per °C; 95% CI: 1.15–1.93; p = 0.002). The model showed good fit (Hosmer–Lemeshow p = 0.326). Conclusions: Patients presenting with hypertension, solid organ tumor, or elevated body temperature at the ED are more likely to have E. coli bacteremia than S. aureus. These predictors may support early empirical antibiotic decision-making.